2011
DOI: 10.1007/s11130-011-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Industrial Onion Wastes (Allium cepa L.): Dietary Fibre and Bioactive Compounds

Abstract: The food industry produces a large amount of onion wastes, making it necessary to search for possible ways for their utilization. One way could be to use these onion wastes as a natural source of high-value functional ingredients, since onion are rich in several groups of compounds, which have perceived benefits to human health. The objective of this work is to gain knowledge of any differences between the different onion wastes obtained from industry and non-commercial bulbs to use them as food ingredients ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
159
1
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(178 citation statements)
references
References 38 publications
13
159
1
5
Order By: Relevance
“…The absorbance of the mixture was measured at 760 nm after incubation for 2 h at room temperature. Gallic acid was used as a reference standard, and the results were expressed as milligram gallic acid equivalents (mg GAE)/100 g wet weight of onion sample (Benítez et al 2011;Nile & Khobragade 2011b TAS TPC TAS TPC TAS TPC TAS TPC TAS TPC Red Bulbs 50.18 ± 1.1 132 ± 1.2 12.1 ± 0.02 92 ± 1.2 25.16 ± 1.1 186 ± 2.2 22.3 ± 1.7 152 ± 5.2 5.2 ± 0.8 62 ± 1.3 White Bulbs 35.6 ± 1.7 112 ± 1.9 8.2 ± 0.4 78 ± 2.1 18.5 ± 1.8 156 ± 1.5 20.1 ± 2.5 140 ± 7.8 2.2 ± 0.6 56 ± 1.1 Yellow Bulbs 42.2 ± 1.2 120 ± 1.8 10.5 ± 0.8 81 ± 1.8 22.1 ± 1.0 165 ± 2.9 24.1 ± 1.9 144 ± 1.9 3.5 ± 0.2 68 ± 1.5…”
Section: Total Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance of the mixture was measured at 760 nm after incubation for 2 h at room temperature. Gallic acid was used as a reference standard, and the results were expressed as milligram gallic acid equivalents (mg GAE)/100 g wet weight of onion sample (Benítez et al 2011;Nile & Khobragade 2011b TAS TPC TAS TPC TAS TPC TAS TPC TAS TPC Red Bulbs 50.18 ± 1.1 132 ± 1.2 12.1 ± 0.02 92 ± 1.2 25.16 ± 1.1 186 ± 2.2 22.3 ± 1.7 152 ± 5.2 5.2 ± 0.8 62 ± 1.3 White Bulbs 35.6 ± 1.7 112 ± 1.9 8.2 ± 0.4 78 ± 2.1 18.5 ± 1.8 156 ± 1.5 20.1 ± 2.5 140 ± 7.8 2.2 ± 0.6 56 ± 1.1 Yellow Bulbs 42.2 ± 1.2 120 ± 1.8 10.5 ± 0.8 81 ± 1.8 22.1 ± 1.0 165 ± 2.9 24.1 ± 1.9 144 ± 1.9 3.5 ± 0.2 68 ± 1.5…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Previous studies reported that onion contains various phenolics, fiber and flavonoids in skin and external layers of onions are relatively high. In addition onion bulbs also contain sulfurous compounds and fructans (a type of oligosacchride) that could be beneficial for human health (Benítez et al 2011;Jang et al 2013). Regarding the onion sections, a decrease in phenolic content was observed from outer to inner sections.…”
Section: Phenolics and Antioxidant Activitymentioning
confidence: 99%
“…This high level of production gives as a result more than 500,000 tons of onion skin waste (OSW) which are discarded within the European Union every year [117]. Therefore, the resulting wastes and by-products have become a major problem [118].…”
Section: Valorization Of Onion By-productsmentioning
confidence: 99%
“…The onion waste has been identiied as a potential source of lavor compounds, dietary iber components, nonstructural carbohydrates like fructans and fructooligosaccharides, and lavonoids particularly quercetin glycosides [117,122]. Most of the studies have been performed at a laboratory scale, so further research is necessary in order to scale up these processes to the industry requirements, assessing their economical viability.…”
Section: Valorization Of Onion By-productsmentioning
confidence: 99%
“…Byproducts derived from crops often contain dietary fiber (DF), which has been reported to have physiological functions. [2][3][4] Blood cholesterol is known to be a risk factor for atherosclerosis and cardiovascular disease, 5) and lowering its level is desirable. In Japan, potatoes are sometimes used in producing alcoholic beverages such as shochu.…”
mentioning
confidence: 99%